Sejarah Daulat Abbasiah - Yusuf Sou'yb (Bulan Bintang, 1977)
ir, jil.1,c.1-2/tr, jil.2=c.1-2/oen, jil.1=c.3-4/tr, jil.2=c.3/ir,jil.1,c.5/why, jil.3=c.1/tr, jil.2=c.4/isr,jil.1=c.6/en, jil.3=c.2/en, jil.1=c.6/en, jil.2=c.5